2018
DOI: 10.3389/fmed.2018.00301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bronchoscopy on Gas Exchange and Respiratory Mechanics in Critically Ill Patients With Atelectasis: An Observational Cohort Study

Abstract: Background: Atelectasis frequently develops in critically ill patients and may result in impaired gas exchange among other complications. The long-term effects of bronchoscopy on gas exchange and the effects on respiratory mechanics are largely unknown.Objective: To evaluate the effect of bronchoscopy on gas exchange and respiratory mechanics in intensive care unit (ICU) patients with atelectasis.Methods: A retrospective, single-center cohort study of patients with clinical indication for bronchoscopy because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In line with these observations, in our study, more bronchoscopies at risk in ICUs were referred to trained pulmonologists, whereas most routine bronchoscopies with lower inherent risk might have been performed by intensivists outside the study population. The published small studies on bronchoscopies in ICUs state consistently higher complications rates comparable to our data, most commonly transient desaturation/hypoxaemia, bleeding, and arrhythmia [17, 18, 29, 39, 47-49]. Low complication rates were observed mainly in elective bronchoscopies from registries with a low proportion of invasive or complex procedures and patients without severe underlying diseases.…”
Section: Discussion/conclusionsupporting
confidence: 87%
See 2 more Smart Citations
“…In line with these observations, in our study, more bronchoscopies at risk in ICUs were referred to trained pulmonologists, whereas most routine bronchoscopies with lower inherent risk might have been performed by intensivists outside the study population. The published small studies on bronchoscopies in ICUs state consistently higher complications rates comparable to our data, most commonly transient desaturation/hypoxaemia, bleeding, and arrhythmia [17, 18, 29, 39, 47-49]. Low complication rates were observed mainly in elective bronchoscopies from registries with a low proportion of invasive or complex procedures and patients without severe underlying diseases.…”
Section: Discussion/conclusionsupporting
confidence: 87%
“…There are few randomized controlled trials investigating bronchoscopy in acutely ill patients. Two randomized studies demonstrated no benefit of bronchoscopy for the treatment or prevention of lobar atelectasis in comparison with chest physiotherapy [33, 34], whereas other observational studies have found beneficial effects of bronchoscopy (i.e., resolution of atelectasis or improvement of oxygenation, ventilation, and respiratory mechanics) [29, 35]. Atelectasis may be caused by other mechanisms than secretions or airway occlusion by foreign bodies (e.g.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the prediction, the nomogram could serve as a tool to select patients for evaluating the necessity of flexible bronchoscopy. In general, the presence of persistent atelectasis in chest imaging is a strong indicator for flexible bronchoscopy intervention 27,28 . Thus early bronchoscopic examination may be necessary for children with MPP presented with clinical sign of atelectasis, regardless of the presence of BMP.…”
Section: Discussionmentioning
confidence: 99%
“…In the intensive care unit, bronchoscopy is widely used to remove secretions and improve atelectasis. 8 11 Beyond that, bronchoalveolar lavage is performed under endotracheal intubation, and respiratory specimens are collected for microbial detection to guide anti-infection treatments. 12 17 During prehospital and intrahospital first aid, bronchoscopy can be used to intuitively observe the position of the trachea and aid in difficult endotracheal intubation or percutaneous tracheostomy, 18 20 as well as airway management after intubation.…”
Section: Discussionmentioning
confidence: 99%